2012
DOI: 10.1128/ec.05311-11
|View full text |Cite
|
Sign up to set email alerts
|

Bestatin Inhibits Cell Growth, Cell Division, and Spore Cell Differentiation in Dictyostelium discoideum

Abstract: ABSTRACTBestatin methyl ester (BME) is an inhibitor of Zn2+-binding aminopeptidases that inhibits cell proliferation and induces apoptosis in normal and cancer cells. We have usedDictyosteliumas a model organism to study the effects of BME. Only two Zn2+-binding aminopeptidases have been identified inDictyostelium Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…These results suggest that CBP4a is recruited to the nucleolus by NumA1 in a Ca 2+ -dependent manner as previously suggested by Myre and O’Day [36]. Unlike CBP4a, NumA1-binding partner PsaA colocalizes with NumA1 in the nucleoplasm but not the nucleolus [34,35]. …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These results suggest that CBP4a is recruited to the nucleolus by NumA1 in a Ca 2+ -dependent manner as previously suggested by Myre and O’Day [36]. Unlike CBP4a, NumA1-binding partner PsaA colocalizes with NumA1 in the nucleoplasm but not the nucleolus [34,35]. …”
Section: Discussionsupporting
confidence: 80%
“…It was also detected at the nuclear envelope region from prometaphase through telophase. This mitotic redistribution pattern was also similar to that of nuclear PsaA and cdk5, two recently identified cell cycle-linked proteins in Dictyostelium [34,35,42]. It was not possible to determine if FhkA was adjacent to the inner nuclear envelope, outer nuclear envelope, or colocalized with the nuclear envelope, however the pattern was similar to that observed for NumA1.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The role of cisplatin on gene expression in the model has been analysed (Van Driessche et al, 2007), in addition to its regulation of mitogen activated protein kinase phosphatases (Moncho-Amor et al, 2011) and in DNA repair pathways (Gunn et al, 2016). The cellular functions of other anti-cancer treatments, such as bestatin and Poly (ADPribose) polymerase inhibitors have also been analysed in D. discoideum (Kolb et al, 2017, Poloz et al, 2012. Finally, Dictyostelium strains have also been shown to provide a source of novel compounds with anti-proliferative properties that could thus be used as cancer treatments (Honma et al, 2018, Kubohara and.…”
Section: Treating Cancer: Lessons From D Discoideummentioning
confidence: 99%
“…Yeast two hybrid and co-immunoprecipitation analyses revealed that NumA1 not only binds to nucleolar Cbp4a but also to nuclear PsaA. PsaA shares the critical domains of human Psa including GAMEN and Zinc-binding domains and, similarly, is also inhibited by bestatin methyl ester (BME) [60,85]. DdPsaA has been proven to possess defined NLS and NES sequences.…”
Section: Protein Associates Of Nucleolar Proteinsmentioning
confidence: 99%